2010
DOI: 10.1097/pcc.0b013e3181d8e405
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of adverse events in pediatric intensive care units in the United States*

Abstract: AEs and ADEs occur frequently in the PICU setting. These data provide areas of focus for evidence-based prevention strategies to decrease the substantial risk to this vulnerable pediatric population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
129
6
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 143 publications
(153 citation statements)
references
References 35 publications
9
129
6
1
Order By: Relevance
“…Consistent with earlier trigger-based harm detection studies, nearly one half of the harm was deemed preventable. 2,13,14 One of every 4 pediatric admissions in our study had at least 1 identified harm. Our detected harm rate is similar to a recent single-site study, which detected a pediatric harm rate of 37 harm events for every 100 admissions using the adultfocused IHI GTT.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Consistent with earlier trigger-based harm detection studies, nearly one half of the harm was deemed preventable. 2,13,14 One of every 4 pediatric admissions in our study had at least 1 identified harm. Our detected harm rate is similar to a recent single-site study, which detected a pediatric harm rate of 37 harm events for every 100 admissions using the adultfocused IHI GTT.…”
Section: Discussionmentioning
confidence: 99%
“…20 Any patients who were admitted for rehabilitation, to the normal newborn nursery, to day treatment areas, or with a primary discharge diagnosis related to psychiatric or obstetric care were excluded as is consistent with earlier study designs. [12][13][14][15][16][17] A random sample of 100 patients who met the inclusion criteria was selected from each site for review. Institutional review board waiver or approval for this study was granted at each site.…”
Section: Design Setting and Patientsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar to those focused on adult populations, pediatricfocused trigger tools have been found to be more efficient and effective at identifying harms compared with traditional methods. [9][10][11][12][13][14] Trigger tool-derived harm rates in the pediatric population have ranged from 11 drug-related harms per 100 patients in the pediatric acute care environment to 203 all-cause harms per 100 patients in the pediatric ICU. 12,14 Our ability to successfully pursue and demonstrate reduction of all-cause harm in pediatric inpatients will require having an efficient and reliable process for harm identification that can be implemented across disparate sites.…”
mentioning
confidence: 99%
“…[9][10][11][12][13][14] Pediatric-focused trigger tools have been created for the neonatal intensive care unit (ICU), the pediatric ICU, and the general pediatric inpatient environments as harm detection tools. Similar to those focused on adult populations, pediatricfocused trigger tools have been found to be more efficient and effective at identifying harms compared with traditional methods.…”
mentioning
confidence: 99%